Hubungan Antara Kecerdasan Naturalistik , Kecerdasan Emosional dan Motivasi Belajar dengan Hasil Belajar Biologi Siswa - Marwah, Sri; Jufri, Muhammad; Caronge, Muhammad Wiharto (UNM Journal of Biological Education, 2017)
The aim of this research were (i) to describe naturalistic intelligence, emotional intelligence,learning motivation, and Biology learning results; (ii) to assess the relation between naturalisticintelligence and Biology learning results; (iii) to assess the relation between emotionalintelligence and Biology learning results; (iv) to assess the relation between learning motivationand Biology learning results; (v) to assess the relation of naturalistic intelligence, emotionalintelligence, and learning motivation simultaneously with Biology learning results of students inspecial talents class at SMPN 6 Makassar. The research was an ex-post facto with a sample totalof 59 students. The results of the research revealed that naturalistic intelligence, emotionalintelligence, learning motivation, and Biology learning results of students in special talents classat SMPN 6 Makassar were categorized in high category. The naturalistic intelligence and Biologylearning results have correlation coefficient of 0,600, and it can be stated that they have asignificant positive and strong relation. The emotional intelligence and Biology learning resultshave correlation coefficient of 0,524, and it can be stated that they have a significant positive andadequately strong relation. The learning motivation and Biology learning results have correlationcoefficient of 0,606, which shows a significant positive and strong relation. The naturalisticintelligence, emotional intelligence, and learning motivation with Biology learning results havecorrelation coefficient of 0,667, which shows a significant positive and strong relation.